Influence of the number of players and the relative pitch area per player on heart rate and physical demands in youth soccer - Castellano, J.; Puente, A.; Echeazarra, I.; Casamichana, D. (The Journal of Strength and Conditioning Research, 2015)
The aim of this study was to analyze the influence of different large-sided games on the physical and physiological variables in under-13 soccer players. The effects on heart rate (HR) and physical demands of different number of players (NP) (7, 9, and 11) together with the relative pitch area (RPA) (100, 200, and 300 m2) during two 12-minute repetitions were analyzed in this study. The variables analyzed were mean, maximum and different intensity zones of HR; total distance (TD); work:rest ratio (W:R); player load (PL); 5 absolute and 3 relative speed categories. The results support the hypothesis that a change in pitch dimensions affects locomotor activity more than the NP does but also refute the hypothesis that the change in the NP has a greater effect on HR. To be more specific, an increase in the RPA per player (300/200/100 m2) was associated with higher values of the following variables: TD (2,250-2,314/2,003-2,148/1,766-1,845 m), W:R (0.5-0.6/0.4-0.5/0.3 arbitrary unit [AU]), PL (271-306/246-285/229-267 AU), %HRmean (85-88/85-89/81-83%), %HRmax (95-100/97-100/95-98%), and affected the percentage of time spent in both absolute (above 8 km/h) and relative speed (above 40% Vmax) categories (p = 0.05, effect size: 0.31-0.85). These results may help youth soccer coaches to plan the progressive introduction of large-sided games so that task demands are adapted to the physiological and physical development of participants.